STRATEGI PENGEMBANGAN EKONOMI LOKAL: IMPLEMENTASI PERENCANAAN PEMBANGUNAN EKONOMI BERBASIS PEMBERDAYAAN DI KABUPATEN SIDOARJO - Yulita Indah Prasetiari, Mrs. (FIA UB, 2012)
Local Economic Development (LED) strategy in Sidoarjo regency uses a business cluster approach. This is marked by the making of several clusters, one of them is âKampoeng Batik Jetisâ. The research is based on the initial assumption that the making of this cluster is not well planned, by not concerning such factors as implementing agent, supporting institution and facilitator. Objectives of the research are: first, to describe and analyze the implementation of LED at âKampoeng Batik Jetisâ; second, to identify the pushing and restraining factors of LED implementation at âKampoeng Batik Jetisâ; and third, to determine the economic impact of LED implemention to the people of âKampoeng Batik JetisâÂ The research uses a descriptive method and qualitative approach. The data is analyzed using domain analysis. The research shows that the implementation of LED at Kampoeng Batik Jetis is on the partisipatory phase, which mean empowerment process come from both government and people, by government and people and to the people. On this phase, people is actively involved in the development. Unfortunately, the existing condition in Kampoeng Batik Jetis is not supported by the most crusial infrastucture that is parking area. Proven that the making of this cluster to be a tourism destination is not well planned. Driving factors as well as inhibiting factors of the LED implementation in Kampoeng Batik Jetis include: human resources, capital, marketing and institutional. The economic impact of the implementation of LED in Kampoeng Batik Jetis turn out to be very significant, namely the increasing of the craftmen earning by 300%, the increasing revenue of the community and reducing unemployment.